(3OaY eVGQ GdCHOGf HCQV eUQs - (3Ydj Hf QVhGf Hf Ydj Hf LYaQ, CHh GdMSf,J (B453 (3g` s ((3MLGRi Hf YeQ GdfghGJi GdCRgQj s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bUOfG Cf fdNU GdMjGI aj OaY eVGQ GdCHOGf HCQV eUQ , hjLH VQhQI Cf JbOe CSHGH gPg GdeVGQ heGgi s
(3BNQgG (B:s
(3aGdTQhQ GdOfjI GdJi JbHd GdYdGL HSQYI hSghdI CMeO hCaVd ef GdTQhQ GdNHjKI GdJi jYSQ YdGLgG , SjeG hYGbHJgG Bef aCgd eUQ EPG CaVd CNdGbkG hCLhO WQjbI , QSeJ Pdc gGgfG djdMb HeG JbOe Ef TGA Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3hHGdfSNI HYV hQbGJ aGSOI GdJUhjQs
(3hLGA Ydi UaMI GdYfhGf (B: (3gPg QSGdI aj Mce WH Cgd eUQ s
(3haj Mce GdaUhd GdCQHYI heG jMeO ajgG heG ojLJfH HgGs
(3ef JCdja GdTjN GdYdGeI SQi GdOjf GHf GdUGFZ GdMfai GdWHjH s
Keywords: (3GdWHs